Verification of Treatment Planning Algorithms Using Optically Stimulated Luminescent Dosimeters in a Breast Phantom - Gopalakrishnan, Zhenia (J Med Phys, 2018)
AIM: The aim of this study is to measure and compare the surface dose of treated breast and contralateral breast with the treatment planning system (TPS) calculated dose using calibrated optically stimulated luminescent dosimeter (OSLD) in an indigenous wax breast phantom. MATERIALS AND METHODS: Three-dimensional conformal plans were generated in eclipse TPS v. 13 to treat the left breast of a wax phantom for a prescribed dose of 200 cGy. The plans were calculated using anisotropic analytical algorithm (AAA) and Acuros algorithm with 1-mm grid size. Calibrated OSLDs were used to measure the surface dose of treated and contralateral breasts. RESULTS: Large differences were observed between measured and expected doses when OSLDs were read in “reading mode” compared to the “hardware mode.” The consistency in the responses of OSLDs was better (deviation <±5%) in the “hardware mode.” Reasonable agreement between TPS dose and measured dose was found in regions inside the treatment field of treated breast using OSLDs for both algorithms. OSLD measured doses and TPS doses, for the points where the angle of incidence was almost normal, were in good agreement compared to all other locations where the angle of incidence varied from 45° to 70°. The maximum deviation between measured doses and calculated doses with AAA and with Acuros were 2.2% and-12.38%, respectively, for planning target volume breast, and 76% and 77.51%, respectively, for the opposite breast. CONCLUSION: An independent calibration factor is required before using the OSLDs for in vivo dose measurements. With reference to measured doses using OSLD, the accuracy of skin dose estimation of TPS with AAA was better than with Acuros for both the breasts. In general, a reasonable agreement between TPS doses calculated using AAA and measured doses exists in regions inside treatment field, but unacceptable differences were observed for the points lateral to the opposite breast for both AAA and Acuros.